Sum of cubes of even and odd natural numbers
We know that sum of cubes of first n natural numbers is = (n(n+1)/2)2.
Sum of cube of first n even natural numbers 23 + 43 + 63 + ……… + (2n)3
Even Sum = 23 + 43 + 63 + .... + (2n)3 if we multiply by 23 then = 23 x (13 + 23 + 33 + .... + (n)3) = 23 + 43 + 63 + ......... + (2n)3 = 23 (n(n+1)/2)2 = 8(n(n+1))2/4 = 2(n(n+1))2
Example :
Sum of cube of first 4 even numbers = 23 + 43 + 63 + 83 put n = 4 = 2(n(n+1))2 = 2*(4*(4+1))2 = 2(4*5)2 = 2(20)2 = 800 8 + 64 + 256 + 512 = 800
Program for Sum of cubes of first n even numbers
Sum of cube of first n odd natural numbers We need to compute 13 + 33 + 53 + …. + (2n-1)3
OddSum = (Sum of cubes of all 2n numbers) - (Sum of cubes of first n even numbers) = (2n(2n+1)/2)2 - 2(n(n+1))2 = n2(2n+1)2 - 2* n2(n+1)2 = n2[(2n+1)2 - 2*(n+1)2] = n2[4n2 + 1 + 4n - 2n2 - 2 - 4n] = n2(2n2 - 1)
Example :
Sum of cube of first 4 odd numbers = 13 + 33 + 53 + 73 put n = 4 = n2(2n2 - 1) = 42(2*(4)2 - 1) = 16(32-1) = 496 1 + 27 + 125 + 343 = 496
Please Login to comment...